Designing and managing the Optimum strategic FM supply chain. Issue 4 (26th August 2014) - Pitt, Michael; Chotipanich, Sarich; Amin, Ruhul; Issarasak, Sittiporn
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to overview carefully selected existing literature to enable further analysis directly concerned with facilities management (FM) supply chain structure, components, strategic issues, challenges and risk. Following the key aspects of assembly, design and, most importantly, management of FM supply chain are explored so that a guidance design framework can be put forward. Design/methodology/approach – This paper examines the optimum technique that can be applied by clients and FM service providers where FM functions are outsourced. The paper initially defines the network structure of the FM supply chain and then suggests a conceptual model for making decisions about FM supply chain network at the strategy level. Furthermore, the paper argues for both supply chain design and for critical node micro management in a transparent supply chain environment with the FM acting as the strategic lens through which the focus of the supply chain is achieved. Findings – This paper presents a process for designing and making decisions of FM service supply chain network. The process begins with an examination of the needs of facility services. It is followed by the step of identifying available options in delivering and processing the services. The third stage involves modelling structures of FM supply chain network. Then to make a final decision, all possible models have to be evaluated for their optimisation, both quantitative (cost) and qualitative (performance). At the end, the model with best optimisation should be selected. Originality/value – This paper proposes a conceptual framework for designing facility service supply chain strategy and configuration to fit with the specific nature of facility service demand of a given organisation. The framework, featuring a set of processes including examining demand nature, identifying options available and analysing options, is first aimed at providing an assisting tool in identifying optimum supply chain network/solution of facility services and, second, intends to stimulate further discussions on this continuously evolving and challenging market.